Cyclic Nucleotides in Platelet Function - Haslam, R J; Davidson, M M L; Fox, J E B; Lynham, J A (Thrombosis and Haemostasis, 1978)
Inhibition of adenylate cyclase in intact platelets by addition of compounds such as 2’, 5’- dideoxyadenosine prevented the inhibition of platelet aggregation by PGE1 but did not affect the responses of platelets to aggregating agents in the absence of PGE1. This confirms that cyclic AMP mediates the effects of PGE1 but indicates that the level of cyclic AMP in unstimulated platelets is too low to affect the actions of aggregating agents. Studies on the phosphorylation of proteins in intact 32P-labelled platelets showed that PGE1 increased the phosphorylation of a membrane-bound polypeptide (P24) and prevented the increased phosphorylation of other polypeptides (P47 and P20) that occurred on addition of inducers of the release reaction. It is suggested that the cyclic AMP-dependent phosphorylation of P24 stimulates the active transport of Ca2+ out of the platelet cytosol, so preventing phosphorylation of P47 and P20, reactions which may be involved in the release mechanism. As increases in platelet cyclic GMP could be dissociated from both platelet aggregation and the release reaction, it is proposed that the bidirectional regulation of platelet function is achieved primarily by the opposing actions of increases in the concentrations of Ca2+ and cyclic AMP.